PENGARUH BURNOUT TERHADAP MOTIVASI BERPRESTASI DALAM BEKERJA PADA SALES - Yeni Yeni; Idah Niswati (Psibernetika, 2012)
Farber (Nevi Dkk, 2005) says that burnout is a response from an individual towards stress he experience in the workplace with sign like physical exhaustion dan emotional, helpless feeling, and negative self concepts that start to grow toward his work and his personal life. Gunarsa and Gunarsa (Ninawati, 2002) says that achievement motivates is tendency to achieve success or getting on what he wanted. desire to achieve success considered as a drive. Sample in this research is an employee who work as a sales. This researches done with quantitative research methods. Data collection methods in this research done with questionnaires. The result of this research is R Square 0.410 which means 41% achievement motivates affected by burnout. Thus it can be concluded that there is effect on burnout toward achievement motives while working on sales. More higher someone experience burnout, then more lower achievement motivates while working on sales.Keywords: burnout, motivasi berprestasi